A PENERAPAN ALGORITMA SQUENTIAL SEARCH WITH SENTINEL PADA APLIKASI KATALOG BUKU PERPUSTAKAAN - Abdillah, Muhammad Harits; Muntahanah, Muntahanah; Wibowo, Sastya Hendri (UNIVED Press, 2021)
A library is one of the facilities provided by an institution or agency such as a school, college or region. The library functions as a place to store various book collections, educational, research, cultural, informative and also a place for recreation. The process of searching for books in the library takes a lot of time depending on the size of the library and the number of books available. Sometimes the book you are looking for is not owned by the library so visitors will spend a lot of time just looking for the book. For this reason, technological assistance is needed that can help in the process of searching for books in the library. Current technological developments are increasingly rapid because they adapt to human needs. Technology can help people solve problems quickly and easily, thereby saving time and energy. One way is to record all book catalogs in the library. The process of searching for books becomes easier because it can be done through the system by matching strings on the book title, author and publisher. One method that is suitable for searching book catalogs is sequential search with sentinel. Sequential search with sentinel is the process of comparing each array element one by one in a row starting from the first element until the element you are looking for is found or until the last element of the array. Sequential search can be performed on unsorted array elements or ordered array elements.